1992
DOI: 10.1088/0953-8984/4/44/015
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in Ca2-xSrxCuO3(x=0, 0.2 and 0.4): Raman and infrared spectroscopy, and lattice dynamics calculation

Abstract: The polarized Raman spectra of Ca2Cu03, C a l . s S r ~. ~C u O ~ and Ca1.6Sro.rCuO3 single oystals and the IR transmission spenra of Ca~Cu03 and Cal.aSro.rOuO~ have been measured. The frequencies of all I'point phonons of Ca2Cuo3 have been dclermined on the basis of assignment of the one-phonon Raman (4) and IR lines 10 definite normal modes and alculalions of the lattice dynamics. The line assignment is wnsislenl wilh earlier mults for Cal.gSr0.2ChO3 as well BS with the line shifts upon substitution of Sr fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 7 publications
5
36
0
Order By: Relevance
“…Hence, the A g mode phonons could be observed in the c(a, a)c and a(c, c)a scattering configurations. Indeed, they were the only observed features here, and therefore could unambiguously be associated with the Ca movement (307 cm −1 ) and O(1) movement (530 cm −1 ) [3,10] along the c-axis. For reasons unknown, no structure due to the B 1g and B 2g modes was observed.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Hence, the A g mode phonons could be observed in the c(a, a)c and a(c, c)a scattering configurations. Indeed, they were the only observed features here, and therefore could unambiguously be associated with the Ca movement (307 cm −1 ) and O(1) movement (530 cm −1 ) [3,10] along the c-axis. For reasons unknown, no structure due to the B 1g and B 2g modes was observed.…”
Section: Resultsmentioning
confidence: 54%
“…2. Two studies have been previously reported for Sr-doped Ca 2 CuO 3 by Yoshida et al [3] and by Zlateva et al [10] As they used single crystals, the Raman-allowed phonons could be identified. According to group theory, the six Raman active modes ( -point phonons, k = 0) in the space group Immm (D 25 2h ) are 2A g +2B 1g +2B 2g (the other nine modes, 3B 1u +3B 2u +3B 3u , are the IR active).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations